Blended morphologies of plasmonic nanofluids for direct absorption applications. (1st November 2018) - Mallah, Abdul Rahman; Kazi, S.N.; Zubir, Mohd Nashrul Mohd; Badarudin, A.
Graphical abstract: Highlights: Comprehensive approach to develop plasmonic nanofluid for direct solar absorption. Blended plasmonic nanoparticles morphologies for broadband high absorptivity. Finite element method obtains the optical properties of plasmonic nanoparticles. Radiative transfer equation obtains the performance of direct solar collector. Very low concentrations of plasmonic nanoparticles can attain an efficiency of 85%. Abstract: Direct absorption solar collectors were introduced to overcome the limitations of conventional surface absorber collectors. The advances in nanotechnology accompanied with phenomenological discoveries at the nanoscale have allowed the appearance of plasmonic nanofluids, which utilize localized surface plasmon resonance phenomenon that multiplies the extinction efficiency of the plasmonic nanoparticle several times at the resonance wavelength. Silver nanoparticles exhibit a high intensity of the localized surface plasmon, which can be fine-tuned within the broadband 350–1200 nm by tailoring their shape, size and aspect ratio. In this paper, we have numerically investigated the effects of silver nanoparticles' morphology on the localized surface plasmon resonance and on the extinction peaks. Numerical results allow determining the effective morphologies at every band of the solar spectrum. Thus, nanofluids composed of blended Ag nano-morphologies were designed, which can expand the absorbance over the entire solar spectrum. By means of the radiative transfer equation, we found that blended plasmonic nanofluids have the potential to raise the efficiency of the direct solar collector to more than 85% at a very low concentration below 0.001 wt%. Utilization of the blended plasmonic nanofluids are not limited to solar thermal and concentrated solar power applications, but also can be extended into the optical filters in PV/thermal applications.